Odpowiedź :
4.
a) 3*(-7)= -21
(-7)*(-6)= 42
4*(-8)= -32
b) (-9)×(-2)= 18
(-9)*4= -36
(-8)*(-5)= 40
c) (-5)*7= -35
5*(-9)= -45
(-6)*(-8)= 48
5.
-15÷(-5)= 3
-15÷5= -3
15÷(-5)= -3
6.
a) 32÷8= 4
12÷6= 2
72÷8= 9
81÷9= 9
b) (-16)÷(-8)= 2
(-32)÷(-4)= 8
(-49)÷(-7)= 7
(-24)÷(-3)= 8
c) 18÷(-3)= -6
36÷(-6)= -6
45÷(-5)= -9
64÷(-8)= -8
d) (-42)÷7= -6
(-72)÷9= -8
(-54)÷6= -9
(-27)÷3= -9
1.
a) <
b) >
c) >
d) <
e) >
f) <
2.
a) 10+(-4)= 6
(-9)+2= -7
(-15)+(-10)= -25
b) 3-7= -4
(-2)-5= -7
(-6)-3= -9
c) (-3)-(-4)= 1
5-(-1)= 6
2-(-6)= 8
Moge naj? :D